PENGARUH MUDHARABAH, MUSYARAKAH, DAN PEMBIAYAAN BAGI HASIL LAINNYA DALAM PEMBIAYAAN BAGI HASIL KEPADA BANK LAIN, TERHADAP LABA BERSIH BANK UMUM SYARIAH DAN UNIT USAHA SYARIAH PERIODE 2008-2021 - Thantawi, Tubagus Rifqy; Damayanti; Putri, Febi Rahayu; Putri, Yulia Kania (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2023)
The aim of this research is to find out whether Profit Sharing Financing to Other Banks in terms of Mudharabah, Musyarakah, and Other Profit Sharing Financing/Others, has a partial and simultaneous effect on Net Profit. Then, to find out what proposals there are for contracts regarding Profit Sharing Financing to Other Banks in terms of Mudharabah, Musyarakah, and Other Profit Sharing Financing, can have a better influence on Net Profit. Based on the analysis and discussion in this research, it can be concluded that the variable Profit Sharing Financing to Other Banks in terms of Mudharabah and Musyarakah and Other Profit Sharing/Others, does not have a partial effect on Net Profit, but has a simultaneous effect on Net profit.